Tanggung Jawab Hukum Platform Shopee Atas Penjualan Barang Palsu: Analisis Pasal 1365 KUHPerdata dan Aspek Perlindungan Konsumen - Bunga Lexsa Angelia; Devi Raisa Fauziah; Shintia Purnama Dewi; Aneza Putri Setiadi; Rosmatun Aliyah (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The development of electronic commerce through marketplace platforms presents new challenges in civil law enforcement, particularly concerning the platform's liability for the circulation of counterfeit goods. This study aims to analyze Shopee's legal responsibility as a provider of electronic transaction services regarding the sale of counterfeit goods, based on Article 1365 of the Civil Code concerning Unlawful Acts and its relation to consumer protection principles as regulated in the Republic of Indonesia Law Number 8 of 1999 concerning Consumer Protection. The research uses a normative juridical method with a legislative approach and literature study, including provisions in the Law on Electronic Information and Transactions and Government Regulation Number 71 of 2019 on the Implementation of Electronic Systems and Transactions. The research findings indicate that although Shopee does not act as a direct seller, the platform still has a legal obligation to provide a reliable, secure, and responsible electronic system. Negligence in verifying sellers and monitoring products has the potential to fulfill the elements of unlawful acts, particularly the elements of fault and causal relationship with consumer losses. This study emphasizes that Shopee qualifies as a business actor in the context of consumer protection, thereby bearing both preventive and repressive responsibilities to ensure transaction security and prevent the circulation of counterfeit goods on its platform.